E-life : web-enabled convergence of commerce, work, and social life : 15th Workshop on e-Business, WEB 2015, Fort Worth, Texas, USA, December 12, 2015, revised selected papers /: web-enabled convergence of commerce, work, and social life : 15th Workshop on e-Business, WEB 2015, Fort Worth, Texas, USA, December 12, 2015, revised selected papers. (2016) - Unknown
No abstract available